Clostridioides difficile Infection in Patients with Cirrhosis Treated for Hepatic Encephalopathy - Sehgal, Kanika; Spiceland, Clayton M.; Lennon, Ryan J.; Pardi, Darrell S.; Khanna, Sahil (Journal of Gastrointestinal Infections, 2023)
Introduction Hospitalizations, proton-pump inhibitors (PPI), and systemic antibiotics increase the risk of Clostridioides difficile infection (CDI) in cirrhosis. We compare the risk of CDI with hepatic encephalopathy (HE) medications, hypothesizing that rifaximin may decrease CDI risk.Materials and Methods A retrospective study of hospitalized HE patients treated with lactulose and/or rifaximin at Mayo Clinic Minnesota, Florida, and Arizona from 2008 to 2013 was conducted. Data on demographics, hospitalizations, antibiotics, and PPI use and CDI were gathered. Univariate and multivariable cox models were constructed.Results We found 1,112 hospitalizations in 1,055 unique patients (55 had 1 subsequent readmission, 1 patient had 2); 428 (40.6%) patients were women (median age: 58 years [interquartile range: 52–65]). CDI developed after 66/1,112 (5.9%) hospitalizations within 12 months post-discharge. Lactulose was administered in 21 (31.8%), rifaximin in 5 (7.6%), both in 40 (60.6%) hospitalizations. Systemic antibiotics were used in 28 (42.4%) patients and PPIs in 60 (90.9%) patients.Univariate analysis using medication (with lactulose alone as the reference group) showed rifaximin was not significantly associated with CDI compared with lactulose (hazard ratio [HR]: 1.57, 95% confidence interval [CI]: 0.57–4.33, p = 0.39). Use of both medications was not significant compared with lactulose (HR: 1.41, 95% CI: 0.84–2.38, p = 0.19). Results were similar after controlling for confounders. Multivariable analysis based on length of stay, age, and gender showed no differences between rifaximin versus lactulose and both versus lactulose.Conclusion There is no significant difference between lactulose and rifaximin on CDI development in HE patients. However, CDI should still be considered when managing diarrhea in HE patients.
Keywords: cirrhosis; Clostridioides difficile; hepatic encephalopathy; lactulose; rifaximin